Introduction to Technology and Its Impact on the Indonesian Migrant Children in Malaysia - Firdaus Firdaus; Andro Dewanta Noegroho; Aldiva Qolby Tiara; Fiderius Ismanto; M. Roby Jatmiko; Wa Ode Sitti Nurrahmah; Kukuh Mulyanto; Asepta Hendriyanto; Alis Arifa Rahman; Ellen Proborini; Heru Yulianto; Nuruddin Mahmud (Jurnal PKM Manajemen Bisnis, 2026)
This community service program addressed the digital literacy gap among Indonesian migrant children at SB Pandan Jaya, Malaysia, who face limited access to digital resources and online safety education. The initiative aimed to strengthen students’ foundational digital skills, promote safe and ethical internet use, and equip teachers with practical tools to facilitate sustained digital literacy. The program was implemented in October 2025 at SB Pandan Jaya, involving 43 students aged 8–15 and 8 teachers, with 12 facilitators from Universitas Muhammadiyah Semarang, STIE Anindyaguna, and STT Pati. A mixed-method participatory approach was employed, combining pre- and post-assessments, classroom observations, reflective interviews, hands-on workshops, and simulated online scenarios. The intervention followed four stages: needs assessment, capacity building and training, guided practice and mentoring, and evaluation and monitoring. Findings indicate significant improvements in student competencies: basic internet knowledge increased by 94%, device operation by 80%, digital safety by 113%, and educational application use by 76%. Teachers’ capacity to integrate ICT and monitor students’ online safety also improved by 61% on average. High attendance and active engagement demonstrated the relevance and effectiveness of the program. Practical sessions and structured guidance enabled students to apply digital skills confidently while fostering safe online behavior. Overall, this program highlights the importance of community-based digital literacy initiatives in enhancing technological readiness and promoting safe internet practices among marginalized migrant children.